2009
DOI: 10.1182/blood-2008-10-183582
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling a novel Rac1-mediated signaling pathway that regulates cofilin dephosphorylation and secretion in thrombin-stimulated platelets

Abstract: In platelets stimulated by thrombin to secrete and aggregate, cofilin is rapidly dephosphorylated leading to its activation. Cofilin by severing existing actin filaments and stimulating F-actin polymerization on newly created barbed ends dynamizes the actin cytoskeleton. We previously found that cofilin dephosphorylation is Ca 2؉ -dependent and occurs upstream of degranulation in stimulated platelets. We report now in thrombinstimulated platelets that Rac1 and class II PAKs (PAK4/5/6) were rapidly (within 5 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 50 publications
(88 reference statements)
8
57
2
Order By: Relevance
“…Both GTPases can modulate platelet secretion (47)(48)(49), and several reports have described impaired secretion in Rac1-null platelets (49) or in NSC23766-treated platelets (48). In our study, TGF-␤1 secretion diminished when platelets were treated with the Rac1 inhibitor NSC23766, as was cytokine release from OG-permeabilized platelets reconstituted with N17Rac1.…”
Section: Discussionsupporting
confidence: 65%
“…Both GTPases can modulate platelet secretion (47)(48)(49), and several reports have described impaired secretion in Rac1-null platelets (49) or in NSC23766-treated platelets (48). In our study, TGF-␤1 secretion diminished when platelets were treated with the Rac1 inhibitor NSC23766, as was cytokine release from OG-permeabilized platelets reconstituted with N17Rac1.…”
Section: Discussionsupporting
confidence: 65%
“…16,17 In addition, Rac1 is reportedly required for thrombus stabilization in conventional in vivo thrombosis models entailing thrombin-stimulated actin reorganization, 16 and in thrombin-stimulated granule secretion. 41 When we assessed thrombus formation in platelet-specific Rac1 KO mice (platelet factor 4 promoter-dependent deletion of Rac1: Pf4-Rac1 KO), we found that only the late-phase thrombus stabilization was impaired, but the effect of Pf4-Rac1 KO was modest in comparison to Y747A KI ( Figure 7D-F, and 7H-J). This finding indicates that both thrombin-PAR signaling-mediated integrin activation and Rac1 activation may be involved in thrombus stabilization, but not in initial platelet adhesion, and further confirm that tyrosine phosphorylation at Y747 of ␤3 integrin is likely required for stable adhesion of thrombi to the endothelium.…”
Section: Org Frommentioning
confidence: 94%
“…Cofilin is known to be activated by, among others, Rac (22). Higher activities for both Rac and cofilin in ␤Arr1 Ϫ/Ϫ MEFs suggest that they function in the same pathway following ␤Arr1 Rac GTP FIGURE 3.…”
Section: Reduction Of Cofilin Phosphorylation In ␤Arr1mentioning
confidence: 99%